A Visit by the UMP New Vice Chancellor - Ezihaslinda, Ngah (2019)
Pekan, 26 June 2019 – The newly appointed UMP Vice-Chancellor (VC), Professor Ir. Dr. Wan Azhar Wan Yusoff, called for a mini get-together with staff members of Centre for Modern Languages and Human Sciences(CMLHS) and the Faculty of Electrical and Electronics Engineering (FEEE) at CMLHS Main Hall, Pekan campus.